A qualitative study of gestational weight gain goal setting - Criss, Shaniece (BMC Pregnancy Childbirth, 2016)
BACKGROUND: Gestational weight gain (GWG) is an important predictor of short and long-term pregnancy outcomes for both mother and child, and women who set a GWG goal are more likely to gain within recommended ranges. Little information is available regarding potentially modifiable factors that underlie a woman’s GWG goals. Our aims were to explore women’s perceptions regarding factors that affect GWG, their understanding of appropriate GWG, their goal-setting experiences including patient-health care provider (HCP) conversations, and supportive interventions they would most like to help them achieve the recommended GWG. METHODS: We conducted nine in-depth interviews and seven focus groups with a total of 33 Boston, Massachusetts (MA) area women who were pregnant and had delivered within the prior 6 months. We recorded and transcribed all interviews. Two investigators independently coded resulting transcripts. We managed data using MAXQDA2 and conducted a content analysis. RESULTS: Perceived factors that contributed to GWG goal-setting included the mother’s weight control behaviors concerning exercise and diet—including a “new way of eating for two” and “semblance of control”, experiences during prior pregnancies, conversations with HCPs, and influence from various information sources. Women focused on behaviors with consistent messaging across multiple sources of information, but mainly trusted their HCP, valued one-to-one conversations with them about GWG, preferred that the HCP initiate the conversation about GWG goals, and would be open to have the conversation started based on visual aid based on their own GWG progression. CONCLUSIONS: Pregnant women highly value discussions with their HCP to set GWG goals. Pregnant women view their clinicians as the most reliable source of information and believe that clinicians should open weight-related discussions throughout pregnancy.